Peran Strategis Baitul Maal Wat Tamwil dalam Menyediakan Pembiayaan Syariah Berbasis Leasing dan Modal Ventura - Afna Eka Widyastuti; Mukhtar Lutfi (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to analyze the strategic role of Baitul Maal Wat Tamwil (BMT) in providing leasing based sharia financing (ijarah) and ventura capital (mudharabah and musyarakah) for Micro, Small and Medium Enterprises (MSMEs) in Indonesia. BMT functions as a microfinance institution that provides solutions to the capital challenges faced by MSMEs, including lack of access to conventional financing and low sharia financial literacy. Through the leasing scheme, BMT facilitates the rental of assets needed by MSMEs without requiring large initial capital. Meanwhile, the venture capital scheme allows BMT to share risks and profits with MSME actors, encouraging strategic collaboration. This study also discusses the challenges of implementing sharia financing by BMT, including the low public understanding of sharia products. With a descriptive literature approach, this study finds that BMT has significant potential in increasing financial inclusion and encouraging the sustainability of the sharia economy in Indonesia.